Investigating the effect of residual stress on hydrogen cracking in multi-pass robotic welding through process compatible non-destructive testing. (March 2021) - Javadi, Yashar; Sweeney, Nina E.; Mohseni, Ehsan; MacLeod, Charles N.; Lines, David; Vasilev, Momchil; Qiu, Zhen; Mineo, Carmelo; Pierce, Stephen G.; Gachagan, Anthony
Graphical abstract: Highlights: Welding Residual Stress (WRS) effect on Hydrogen Induced Cracking (HIC) is studied. HIC test samples with high and low WRS are repeatably manufactured. Offline Non-Destructive Testing (NDT) and high-temperature in-process NDT are used. WRS, measured using hole-drilling method, is higher in the sample with larger HIC. Real-time monitoring of relationship between WRS and HIC is achieved. Abstract: In this paper, the effect of Welding Residual Stress (WRS) on the size and morphology of hydrogen-induced cracks (HIC) is studied. Four samples were manufactured using a 6-axis welding robot and in two separate batches. The difference between the two batches was the clamping system used, which resulted in different amounts of welding deformation and WRS. The hydrogen cracks were intentionally manufactured in the samples using a localised water-quenching method, where water was sprayed over a specific weld pass in a predetermined position. The Phased-Array Ultrasonic Testing (PAUT) system was implemented during the welding process (high-temperature in-process method), to detect the HIC in real-time. The WRS in both batches was measured using the hole-drilling method, where a difference in transversal residual stress of 78 MPa was found between the two samples. Based upon both the PAUT results and microscopic investigations, the batch with higher WRS resulted in larger size and number of HIC. For the first time, the negative effect of WRS on HIC has been monitored in real-time using high-temperature in-process inspection. This was achieved using an innovative approach, introduced in this paper, to repeatably manufacture high and low WRS samples in order to control the size and location of subsequent HIC.